Improving Mental Health Through Art Therapy on Rohingya Refugee Children - Maria Ulfa; Irma Oktaianti; Shinta Devi (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2024)
Rohingya is an ethnic group living in the northern city of Rakhine in the western region of Myanmar. The Rohingya ethnic group suffers discriminatory treatment and various forms of human rights violations. Starting from losing the right to worship, difficulties in access in the employment sector, the health sector, restrictions on the number of children and access to formal education, it is very natural that the percentage of Rohingya ethnic illiterates reaches 80%. Therefore, until now there is still a wave of flight and displacement of the Rohingya ethnic group which has spread to various countries including Indonesia, especially Aceh. The service activities carried out by the psychology team took place in the Ladong area, Aceh Besar in collaboration with Rumoh Seujahtera Aneuk Nangroe (RSAN). The drawing activity carried out by the service team is carried out once a week for one month, apart from carrying out drawing therapy, the children also tell the contents of what is being drawn. Ronghiya children look happy and happy with this drawing activity because they can express what they feel through drawing and telling stories. Keywords: Rohingya Children, Mental Health, Art Therapy.